A pseudo-bilayer organic photoanode for solar water oxidation - Gyu Won Chae; Seong Rae Kang; Jin Su Park; Euimin Lee; Jisu Yoo; Hyuna Kim; Jongbeom Kim; Hoon Kim; Donghyun Lee; Eunsong Jeon; Wonjun Kim; Changduk Yang; et al. (Chemical Engineering Journal, 2026)

Effect of fat content on the inactivation of foodborne pathogens in pork sausage using 915 MHz microwave heating - Su-Yeon Kang; Eun-Rae Cho; Do-Kyun Kim; Dong-Hyun Kang (Food Control, 2026)

CFD-informed surrogate modeling for rapid prediction of coupled pavement–air thermal response - Hamidreza Alinejad; Junsuk Kang; Junmo Lee; Young Sun Kwon; Seunghun Baek; Jung-Min Lee; Sang Rae Kim (Building and Environment, 2026)

High-Throughput Sequencing-Guided Development and Validation of an RT-dPCR Assay for Sensitive Detection of Lentinula edodes Spherical Virus in Shiitake Mushrooms - Min-Jae Kim; Chae-Min Kang; In-Gyeong Kim; Rae-Dong Jeong (Current Microbiology, 2026)

Optimization of MS-222 Concentration for Short-Term Handling of Juvenile Pseudopungtungia nigra Based on Induction and Recovery Responses - Kang-Rae Kim; In-Chul Bang (Fishes, 2026)
The black shinner Pseudopungtungia nigra is an endangered freshwater fish endemic to Korea, and standardized anesthetic protocols are needed for conservation-related hatchery handling. This study evaluated the effects of water temperature and MS-222 concentration on anesthetic induction and recovery responses in hatchery-reared juvenile P. nigra of approximately 3 cm total length. Juveniles were exposed to four MS-222 concentrations, 80, 100, 150, and 200 mg L−1, at three water temperatures, 21, 24, and 27 °C. Induction time, recovery time, and recovery success within 600 s were assessed using behavioral endpoints. The 80 mg L−1 treatment induced anesthesia within 600 s only at 27 °C, whereas fish exposed at 21 and 24 °C failed to reach the defined anesthetic stage within 600 s; therefore, this treatment was treated as a low-concentration induction-failure condition. In the main 3 × 3 factorial analysis using 100, 150, and 200 mg L−1, induction time decreased significantly with increasing MS-222 concentration and water temperature, with significant effects of temperature, concentration, and their interaction. In contrast, recovery time increased with increasing MS-222 concentration, indicating a clear trade-off between rapid induction and recovery stability. Although 200 mg L−1 produced the shortest induction times, it also resulted in the longest recovery times and delayed recovery at 24 and 27 °C. The 100 mg L−1 treatment showed stable recovery but required prolonged induction, especially at lower temperatures. Overall, 150 mg L−1 provided the most balanced behavioral response by substantially reducing induction time compared with 100 mg L−1 while avoiding the greater recovery burden observed at 200 mg L−1. These findings suggest that 150 mg L−1 MS-222 is a practical concentration for routine short-term handling of hatchery-reared juvenile P. nigra under the tested temperature and handling conditions. However, this recommendation should be interpreted as a behavioral handling guideline because physiological stress responses and long-term post-anesthetic outcomes were not evaluated.

Assessing Genetic Diversity and Population Structure of the Endangered Freshwater Fish Gobiobotia brevibarba for Conservation Genetics in Korea - Keun-Sik Kim; Kang-Rae Kim; In-Chul Bang (Fishes, 2025)
The endangered freshwater fish Gobiobotia brevibarba is endemic to Korea and threatened by habitat disturbance in major river systems. We investigated four wild populations from the Han River basin (IJR, BHR, NHR) and the Geum River basin (GR) using eleven microsatellite loci to assess genetic diversity, population structure, and contemporary gene flow. All populations showed relatively high genetic diversity (HO = 0.709–0.800, HE = 0.707–0.803) and no evidence of inbreeding, although bottleneck signals under the infinite allele mutation model were detected in IJR and BHR. Contemporary effective population size was large in IJR (Ne = 2463) and moderate in NHR (Ne = 467), whereas estimates for BHR and GR were imprecise. Genetic differentiation was very low within the Han River basin (FST = 0.009–0.027) but weak and significant between Han and Geum (FST = 0.085–0.096), and clustering analyses (STRUCTURE, DAPC, find.cluster) consistently supported K = 2, separating Han from Geum River. Gene flow analyses indicated extremely limited interbasin gene flow (

Microsatellite-Based Evaluation of Genetic-Distance-Driven Crossbreeding in the Endangered Freshwater Fish Pseudopungtungia nigra - Kang-Rae Kim; In-Chul Bang (Fishes, 2025)
Artificial crossbreeding is a critical strategy in the restoration of endangered freshwater fishes with small, fragmented populations, where natural spawning alone cannot reverse genetic erosion. This study examined the genetic diversity and fitness traits of crosses between genetically distant (HGD) and closely related (LGD) broodstock individuals of Pseudopungtungia nigra, an endangered Korean freshwater fish. Using ten microsatellite loci, we evaluated genetic diversity, population structure, and early survival performance among crossbreeds and their broodstock. Both HGD and LGD progenies showed deviations from Hardy–Weinberg equilibrium and exhibited higher observed heterozygosity than expected, indicating the influence of artificial selection. The broodstock and both crossbred groups displayed bottleneck signals, while LD-based effective population size was infinite for the broodstock and HGD but finite for LGD, suggesting estimation bias because the parameter was undeterminable due to small sample size (each group, n = 28–30). STRUCTURE and DAPC analyses revealed that HGD_20 was most genetically similar to the broodstock population, while LGD and HGD_19 formed distinct clusters. Hatching rate was 1.5-fold higher in HGD compared with LGD (p 0.05). These results highlight that crossbreeding based on genetic distance can enhance genetic diversity and hatching performance without causing excessive genetic divergence from the parental population, offering a practical model for the genetic management of endangered fish restoration.

Robust Relative Space Motion Control of Underwater Vehicles Using Time Delay Estimation - Gun Rae Cho; Hyungjoo Kang; Min-Gyu Kim; Sungho Park; Chulhee Bae; Han-Sol Jin; Seongho Jin; Ji-Hong Li (Journal of Marine Science and Engineering, 2025)
This paper presents a robust trajectory-tracking control framework for underwater vehicles operating in a relative coordinate system. Unlike conventional methods that define trajectories in the world frame, the proposed approach formulates the control problem directly in a moving reference frame, enabling accurate motion control with respect to dynamic and drifting objects affected by environmental disturbances such as ocean currents and waves. This relative-space formulation is particularly advantageous for tasks including diver guidance, floating-object inspection, and docking, where the reference itself is nonstationary. A coordinate transformation is introduced to consistently express the vehicle dynamics in the relative frame. Based on the transformed dynamics, a Time Delay Control (TDC) law is applied to estimate unmodeled dynamics and external disturbances without requiring precise system parameters. Theoretical stability analysis shows that the stability condition of the proposed controller is consistent with that of conventional TDC, allowing similar gain-tuning procedures. Simulation results demonstrate that the proposed controller achieves robust and smooth trajectory tracking even when the reference frame undergoes motion induced by ocean currents.

First report of euphorbia ringspot virus infecting Euphorbia milii in Korea - Ji-Min Kang; Min-Jae Kim; Rae-Dong Jeong (Journal of Plant Pathology, 2025)

Estimation of Hydrodynamic Coefficients for the Underwater Robot P-SUROII via Constraint Recursive Least Squares Method - Hyungjoo Kang; Ji-Hong Li; Min-Gyu Kim; Hansol Jin; Mun-Jik Lee; Gun Rae Cho; Sangrok Jin (Journal of Marine Science and Engineering, 2025)
This study proposes a system identification (SI) technique based on the constrained recursive least squares (CRLS) method to model the dynamics of the P-SUROII. By simplifying the dynamic model in consideration of the inherent characteristics of underwater vehicles and minimizing the number of parameters to be estimated, the proposed approach aims to improve estimation accuracy. In addition, a simplified thruster input model was applied to quantify the actual thruster output and improve the reliability of the input data. To satisfy the persistent excitation (PE) condition during the estimation process, experiments incorporating various motion modes were designed, and free-running and S-shaped maneuvering tests were additionally conducted to validate the model’s generalization capability and prediction performance. The coefficients estimated using the CRLS method, which is robust to noise and bias, were evaluated using quantitative similarity metrics such as root mean squared error (RMSE) and mean absolute error (MAE), confirming their validity. The proposed method effectively captures the actual dynamics of the underwater vehicle and is expected to serve as a key enabling technology for the future development of high-performance control systems and autonomous operation systems.

Engineering robust interfaces for enhanced Li metal and ceramic electrolyte compatibility in solid-state systems - Rae-Hyun Lee; Ha-Na Jo; Chea-Yun Kang; Jong-Kyu Lee; Hyun-Soo Kim; Bong-Soo Jin; Kyong-Nam Kim; Jung-Rag Yoon; Seung-Hwan Lee (Chemical Engineering Journal, 2024)

Population Structure Using Mitochondrial DNA for the Conservation of Liobagrus geumgangensis (Siluriformes: Amblycipitidae), an Endemic Freshwater Fish in Korea - Kang-Rae Kim; Mu-Sung Sung; Keun-Sik Kim (Fishes, 2024)
Liobagrus geumgangensis is a novel Korean fish species endemic to the Geumgang and Mangyeonggang River basins on the Korean Peninsula. During a survey of L. geumgangensis, the discovery of Liobagrus mediadiposalis as a potential threat prompted an investigation into L. geumgangensis genetic diversity and structure. Three populations of L. geumagangensis and one population of L. mediadiposalis were investigated using a 1024-bp sequence in the cytb region of mitochondrial DNA. The Mangyeonggang River of L. geumagangensis displayed the lowest haplotype diversity (Hd) within a range of 0.000–0.337, with one to two haplotypes (h). The Jecheon region of the Geumgang River for L. geumagangensis population had the highest nucleotide diversity (π) and was within the range of 0.00000–0.00066. The h of L. mediadiposalis population was 3, the range of Hd was 0.292, and π was 0.00231. Tajima’s D (D) and Fu’s Fs (F) were negative and non-significant in the LgGJ population. The genetic structure of L. geumgangensis had no shared haplotypes among the three populations. The discovery of L. mediadiposalis in the Geumgang River suggests the necessity of non-habitat conservation and population management of fish farms to conserve L. geumgangensis.

Clinical outcomes and immunological features of COVID-19 patients receiving B-cell depletion therapy during the Omicron era - Chan Mi Lee; Minji Kim; Seong-wook Park; Chang Kyung Kang; Pyoeng Gyun Choe; Nam Joong Kim; Hyeon Jae Jo; Hyun Mu Shin; Chang-Han Lee; Hang-Rae Kim; Wan Beom Park; Myoung-don Oh (Infectious Diseases, 2024)

Genome assembly and microsatellite marker development using Illumina and PacBio sequencing in Persicaria maackiana (Polygonaceae) from Korea - Kang-Rae Kim; So Young Park; Heesoo Kim; Jiyeon Kim; Jeong Min Hong; Sun-Yu Kim; Jeong-Nam Yu (Genes & Genomics, 2024)

First report of natural infection of Vigna angularis by hop stunt viroid in Korea - Chae-Min Kang; Hae-Jun Kim; Rae-Dong Jeong (Journal of Plant Pathology, 2024)

Facile and rapid fabrication of wearable biosensors via femtosecond laser-directed micro-patterning with large-sized reduced graphene oxide for physiological monitoring - Hae-In Moon; Sungil Kim; Jeong Eun Byun; Young Won Kim; Yeon Wook Jung; Seung Geun Jo; Yujin Shin; Yeoul Kang; Sang Jun Kim; Eun-Su Lee; Hyung-Jong Lee; Min-Cheol Oh; et al. (Chemical Engineering Journal, 2024)

Metabolomic analysis reveals linkage between chemical composition and sensory quality of different floral honey samples - Min Jeong Kang; Keup-Rae Kim; Keono Kim; Aria G. Morrill; Chuleui Jung; Sukjun Sun; Dong-Hee Lee; Joon Hyuk Suh; Jeehye Sung (Food Research International, 2023)

Nemopilema nomurai jellyfish venom attenuates phenotypic modulation of PDGF BB-induced vascular smooth muscle cells and κ-carrageenan-induced rat tail thrombosis - Hyeryeon Yang; Seongkyeong Bae; Du Hyeon Hwang; Ramachandran Loganathan Mohan Prakash; Jong-Hyun Kim; Il-Hwa Hong; Woo Hyun Kim; Il Rae Rho; Euikyung Kim; Changkeun Kang (Toxicon, 2023)

Electron uptake from solid electrodes promotes the more efficient conversion of CO2 to polyhydroxybutyrate by using Rhodobacter sphaeroides - Shuwei Li; Minsoo Kim; Da Seul Kong; Kyoungseon Min; Guangxi Wu; Meiying Cui; Changman Kim; You-Kwan Oh; Soek Kim; Soo Youn Lee; Sung Gyun Kang; Yvonne Nygård; et al. (Chemical Engineering Journal, 2023)

An Experimental Study on Trajectory Tracking Control of Torpedo-like AUVs Using Coupled Error Dynamics - Gun Rae Cho; Hyungjoo Kang; Min-Gyu Kim; Mun-Jik Lee; Ji-Hong Li; Hosung Kim; Hansol Lee; Gwonsoo Lee (Journal of Marine Science and Engineering, 2023)
In this paper, we propose a trajectory tracking controller with experimental verification for torpedo-like autonomous underwater vehicles (AUVs) with underactuation characteristics. The proposed controller overcomes the underactuation problem by designing the desired error dynamics in a coupled form using state variables in body-fixed and world coordinates. Unlike the back-stepping control requiring high-order derivatives of state variables, the proposed controller only requires the first derivatives of the states, which can alleviate noise magnification issues due to differentiation. We adopt time delay estimation to estimate the dynamics indirectly using control inputs and vehicle outputs, making the proposed controller relatively easy to apply without requiring the all of the vehicle dynamics. We also address some practical issues that commonly arise in experimental environments: handling measurement noises and actuation limits. To mitigate the effects of noise on the controller, a filtering technique using a moving window average is employed. Additionally, to account for the actuation limits, we design an anti-windup structure that takes into consideration the nonlinearity between the thrusting force and rotating speed of the thruster. We verify the tracking performance of the proposed controller through experimentation using an AUV. The experimental results show that the 3D motion control of the proposed controller exhibits an RMS error of 0.3216 m and demonstrate that the proposed controller achieves accurate tracking performance, making it suitable for survey missions that require tracking errors of less than one meter.

Incipient subsidence and subsequent clockwise rotation of the Miocene Janggi onshore basin, SE Korea, associated with the back-arc opening of East Sea - Min-Cheol Kim; Rae-Yoon Jeong; Gyeonggeol Gahng; Yong-Un Chae; Cheol Woo Song; Hee-Cheol Kang; Moon Son (Marine Geophysical Research, 2023)

CINEMA-SMART development and its application to SBLOCA analysis for Korean small integral reactor - Rae-Joon Park; Donggun Son; Sang Ho Kim; Hyung-Seok Kang; ChangHwan Park (Annals of Nuclear Energy, 2023)

Adaptive Formation Control of Multiple Underactuated Autonomous Underwater Vehicles - Ji-Hong Li; Hyungjoo Kang; Min-Gyu Kim; Mun-Jik Lee; Gun Rae Cho; Han-Sol Jin (Journal of Marine Science and Engineering, 2022)
In this paper, we present a 3D formation control scheme for a group of torpedo-type underactuated autonomous underwater vehicles (AUVs). These multiple AUVs combined with an unmanned surface vessel (USV) construct a sort of star-topology acoustic communication network where the USV is at the center point. Due to this kind of topological feature, this paper applies a virtual school concept. This is a geometric graph where each node is taken as a virtual leader for each specific AUV and assigned its own reference trajectory. For each individual vehicle, its formation strategy is simple: just follow the trajectory of its corresponding virtual leader so as for multiple AUVs to compose the given formation. As for the formation subject, this paper mainly focuses on the formation tracking problem rather than the formation producing. For the torpedo-type vehicle considered in this paper, there are only three control inputs (surge force, pitch, and yaw moments) available for its underwater 3D motion and therefore this is a typical underactuated system. For the following vehicle’s trajectory, a sort of potential field method is used for obstacle avoidance, and a neural network-based adaptive scheme is applied to on-line approximate the vehicle’s unknown nonlinear dynamics, and the uncertainty terms including modeling errors, measurement noises, and external disturbances are handled by the properly designed robust scheme. The proposed formation method can guarantee the uniform ultimate boundedness (UUB) of the closed-loop system. Numerical studies are also carried out to verify the effectiveness of the proposed scheme.

Tomato ARPC1 regulates trichome morphology and density and terpene biosynthesis - Jae-In Chun; Seong-Min Kim; Na-Rae Jeong; Sang Hee Kim; Choonkyun Jung; Jin-Ho Kang (Planta, 2022)

Experimental Study on Tele-Manipulation Assistance Technique Using a Touch Screen for Underwater Cable Maintenance Tasks - Gun Rae Cho; Geonhui Ki; Mun-Jik Lee; Hyungjoo Kang; Min-Gyu Kim; Ji-Hong Li (Journal of Marine Science and Engineering, 2021)
In underwater environments restricted from human access, many intervention tasks are performed by using robotic systems like underwater manipulators. Commonly, the robotic systems are tele-operated from operating ships; the operation is apt to be inefficient because of restricted underwater information and complex operation methods. In this paper, an assistance technique for tele-manipulation is investigated and evaluated experimentally. The key idea behind the assistance technique is to operate the manipulator by touching several points on the camera images. To implement the idea, the position estimation technique utilizing the touch inputs is investigated. The assistance technique is simple but significantly helpful to increase temporal efficiency of tele-manipulation for underwater tasks. Using URI-T, a cable burying ROV (Remotely Operated Vehicle) developed in Korea, the performance of the proposed assistance technique is verified. The underwater cable gripping task, one of the cable maintenance tasks carried out by the cable burying ROV, is employed for the performance evaluation, and the experimental results are analyzed statistically. The results show that the assistance technique can improve the efficiency of the tele-manipulation considerably in comparison with the conventional tele-operation method.

Tomato hairless on stems mutant affects trichome development - Won-Ki Hong; Jae-In Chun; Na-Rae Jeong; Heejin Kim; Jin-Ho Kang (Horticulture, Environment, and Biotechnology, 2021)

Genetic diversity and population structure of the endangered fish Pseudobagrus brevicorpus (Bagridae) using a newly developed 12-microsatellite marker - Yeong Ho Kwak; Kang Rae Kim; Moo Sang Kim; In Chul Bang (Genes & Genomics, 2020)

Microsatellite records for volume 12, issue 2 - In-Chul Bang; Fleur Bruggemann; Chen Chen; Quentin D’Alexis; Hongmei Gao; Pauline Gélin; Xiaoyou Hong; Miho Inoue-Murayama; Kang-Rae Kim; Yeong-Ho Kwak; Wei Li; Haitao Ma; et al. (Conservation Genetics Resources, 2020)

UUV Simulation Modeling and its Control Method: Simulation and Experimental Studies - Ji-Hong Li; Min-Gyu Kim; Hyungjoo Kang; Mun-Jik Lee; Gun Rae Cho (Journal of Marine Science and Engineering, 2019)
This paper presents the development of an unmanned underwater vehicle (UUV) platform, especially the derivation of the vehicle’s simulation model and its control method to overcome strong sea current. The platform is designed to have a flattened ellipsoidal exterior so as to minimize the hydrodynamic damping on the horizontal plane. Four horizontal thrusters with the identical specifications are symmetrically mounted on the horizontal plane, and each of them has the same thrust dynamics in both forward and reverse directions. In addition, there are three vertical thrusters used to handle the vehicle’s roll, pitch and heave motions. Control strategy proposed in this paper to overcome strong current is that: maximizing the vectored horizontal thrust force against the sea current without or with the least of the vehicle’s rotation on the horizontal plane. For the vehicle model, due to it being symmetric in all of three axes, the vehicle dynamics can be simplified and all of hydrodynamic coefficients are calculated through both of theoretical and empirically-derived formulas. Numerical simulations and experimental studies in both of the water tank and the circulating water channel are carried out to demonstrate the vehicle’s capability of overcoming strong current.

Recent advances in intra-articular drug delivery systems to extend drug retention in joint - Myoung Jin Ho; Sung Rae Kim; Young Wook Choi; Myung Joo Kang (Journal of Pharmaceutical Investigation, 2019)

Perfluorooctane sulfonate exacerbates mast cell-mediated allergic inflammation by the release of histamine - Jun-Kyoung Lee; Soyoung Lee; Young-Ae Choi; Meiling Jin; Yeon-Yong Kim; Byeong-Cheol Kang; Min-Jong Kim; Hima Dhakal; Sang-Rae Lee; Sun-Uk Kim; Dongwoo Khang; Sang-Hyun Kim (Molecular & Cellular Toxicology, 2018)

Combined Poly(Lactide-Co-Glycolide) Microspheres Containing Diphtheria Toxoid for a Single-shot Immunization - Hye Seung Woo; Sung Rae Kim; Mikyeong Yoon; Eun Seok Lee; In Ho Chang; Young Mi Whang; Do Ik Lee; Myung Joo Kang; Young Wook Choi (AAPS PharmSciTech, 2018)

Genetic analysis of the tomato inquieta mutant links the ARP2/3 complex to trichome development - Na-Rae Jeong; Heejin Kim; In-Taek Hwang; Gregg A. Howe; Jin-Ho Kang (Journal of Plant Biology, 2017)

Systematic identification of novel biomarker signatures associated with acquired erlotinib resistance in cancer cells - Young Seok Lee; Jin Ki Kim; Tae Hwan Park; Young Rae Kim; Ho Sung Myeong; Kang Kwon; Young Tae Ro; Yun Hee Noh; Sung Young Kim (Molecular & Cellular Toxicology, 2016)

Removal of Iopromide and Its Intermediates from Ozone-Treated Water Using Granular Activated Carbon - Yong-Tae Ahn; Dong-Wan Cho; Akhil N. Kabra; Min-Kyu Ji; Yeojoon Yoon; Jaewon Choi; Il-Hwan Choi; Joon-Wun Kang; Jung Rae Kim; Byong-Hun Jeon (Water, Air, & Soil Pollution, 2015)

Morphological and genetic variability among Ecklonia cava (Laminariales, Phaeophyceae) populations in Korea - Dong Mun Choi; Young Wook Ko; Rae-Seon Kang; Jeong Ha Kim (Algae, 2015)

Ticks collected from migratory birds, including a new record of Haemaphysalis formosensis, on Jeju Island, Korea - Chang-Yong Choi; Chang-Wan Kang; Eun-Mi Kim; Sang Lee; Kyoung-Ha Moon; Mi-Rae Oh; Takeo Yamauchi; Young-Min Yun (Experimental and Applied Acarology, 2014)

Topical formulation of retinyl retinoate employing nanostructured lipid carriers - Sang Gon Lee; Jae Han Jeong; Sung Rae Kim; Kyung Min Lee; Byeong Kil Ahn; Mean Hyung Kang; Young Wook Choi (Journal of Pharmaceutical Investigation, 2012)

UPLC/Q-TOF MS based metabolomics approach to post-mortem-interval discrimination: mass spectrometry based metabolomics approach - Yi-Rae Kang; Yoon Soo Park; Yong Cheon Park; Su Min Yoon; Hee JongAhn; Gijeong Kim; Sung Won Kwon (Journal of Pharmaceutical Investigation, 2012)

Potential involvement of CCL23 in atherosclerotic lesion formation/progression by the enhancement of chemotaxis, adhesion molecule expression, and MMP-2 release from monocytes - Chu-Sook Kim; Ji-Hye Kang; Hong-Rae Cho; Thomas N. Blankenship; Kent L. Erickson; Teruo Kawada; Rina Yu (Inflammation Research, 2011)

Alteration of floral organ identity by over-expression of IbMADS3-1 in tobacco - Mi-Rae Shin; Sang-Gyu Seo; Ji-Seoung Kim; Seo-Bum Joen; Seung-Won Kang; Gung-Pyo Lee; Suk-Yoon Kwon; Sun-Hyung Kim (Transgenic Research, 2011)

The complete mitogenome sequence of the Japanese oak silkmoth, Antheraea yamamai (Lepidoptera: Saturniidae) - Seong Ryeol Kim; Man Il Kim; Mee Yeon Hong; Kee Young Kim; Pil Don Kang; Jae Sam Hwang; Yeon Soo Han; Byung Rae Jin; Iksoo Kim (Molecular Biology Reports, 2009)

Touch-induced gene (IbTCH1) from sweet potato [Ipomoea batatas (L.) Lam.]: molecular cloning and functional analysis - Sang-Gyu Seo; Ji-Seong Kim; Seung-Won Kang; Mi-Rae Shin; You-Sun Yang; Gung-Pyo Lee; Jin-Sung Hong; Sun-Hyung Kim (Plant Biotechnology Reports, 2008)

Compensatory growth and body composition of juvenile black rockfish Sebastes schlegeli following feed deprivation - Sung-Yong OH; Choong Hwan NOH; Rae-Seon KANG; Chong-Kwan KIM; Sung Hwoan CHO; Jae-Yoon JO (Fisheries Science, 2008)

Endoplasmic Reticulum Stress Response of Bombyx Mori Calreticulin - Tae Won Goo; Soojung Park; Byung Rae Jin; Eun Young Yun; Iksoo Kim; Si-kab Nho; Seok-Woo Kang; O-Yu Kwon (Molecular Biology Reports, 2005)

Seaweed Community of the Subtidal Rocky Habitats along the Coast of Geumo Archipelago in the Central South Sea of Korea - Rae-Seon Kang; Jong-Man Kim (Algae, 2004)

Cloning of the fibroin gene from the oak silkworm, Antheraea yamamai and its complete sequence - Jae-Sam Hwang; Jin-Sung Lee; Tae-Won Goo; Eun-Young Yun; Kwang-Sik Lee; Yong-Sung Kim; Byung-Rae Jin; Sang-Mong Lee; Keun-Young Kim; Seok-Woo Kang; Dong-Sang Suh (Biotechnology Letters, 2001)

Morphological and genetic variability among Ecklonia cava (Laminariales, Phaeophyceae) populations in Korea - Dong Mun Choi; Young Wook Ko; Rae-Seon Kang; Jeong Ha Kim (Algae, 1970)